Analisis Persebaran Reptil di Laboratorium Lapang Terpadu Universitas Lampung (Reptile Distribution Analysis in the Integrated Field Laboratory, University of Lampung) - Nimas Ayu Fatmawati; Bainah Sari Dewi; Rusita Rusita; Yulia Rahma Fitriana (Journal of People, Forest and Environment, 2021)
Abstract : Reptiles play an important role in an ecosystem as one part of the food chain and some of them are environmental bio-indicators. The purpose of this study was to obtain information and determine the distribution and presence of reptiles in three habitats. This research was conducted in December 2020-January 2021 at the Integrated Field Laboratory. The method used is a Visual Encounter Survey (VES) or a Visual Encounter Survey with a combination of Time Search and taking the coordinates of the species with GPS. The results were analyzed using the Arcgis 10.3 application and google earth. The results showed that the distribution of reptiles in the three habitats was in the even or homogeneous category. This is due to several factors, such as the availability of food and the adjacent habitat, which makes it easier for reptiles to change locations. Reptiles are indicators of environmental balance that must be identified by conducting monitoring and further research to reduce threats or reptile species such as hunting and trade in liars. Abstrak : Reptil berperan penting dalam suatu ekosistem sebagai salah satu bagian dari penyusun rantai makanan dan beberapa diantaranya merupakan bio-indikator lingkungan. Tujuan dari penelitian ini adalah mendapatkan informasi dan mengetahui persebaran dan keberadaan reptil pada tiga habitat. Penelitian ini dilakukan pada bulan Desember 2020-Januari 2021 di Laboratorium Lapang Terpadu. Metode yang digunakan adalah Visual Encounter Survey (VES) atau Survei Perjumpaan Visual dengan kombinasi Time Search serta mengambil titik koordinat spesies teramati dengan GPS. Hasilnya dianalisis  dengan menggunakan aplikasi Arcgis 10.3 dan google earth. Hasil penelitian menunjukkan bahwa persebaran reptil pada ketiga habitat termasuk ke dalam kategori merata atau homogen. Hal ini disebabkan oleh beberapa faktor seperti ketersediaan pakan dan lokasi habitat yang berdekatan yang memudahkan reptil untuk berpidah lokasi. Reptil adalah indikator keseimbangan lingkungan yang harus diketahui keberadaannya dengan melakukan monitoring dan penelitian lanjutan untuk mengurangi ancaman ataupun gangguan spesies reptil seperti perburuan dan perdagangan liar. Kata kunci : reptil; persebaran jenis; bio-indikator.